Comparison Of Body Mass Index And Bioelectric Impedance Analysis Methods On Determination Of Body Composition In Young Adults - Çolak, Ramis; Özçelik, Oğuz; Aslan, Muammer; Özcan, Mete (Fırat University, 2002)
Aim: To evaluate the validity of body mass index (BMI) and bioelectric impedans analysis (BIA) methods which were used in obesity determination in young adults Materials and Methods: BMI values and measurements of body composition using BIA were obtained from total of 246 student (171 male and 75 female). Results: In males, BMI was found to be (7%) 30 in a subject. In females, BMI was found to be (12%) 30 in a subject. In males, body fat mass percent was found to be (66.8 %) below normal in 114, (29.9%) normal in 51, (2.2%) above normal in 4 and (1.1%) obese in 2 subjects. In females, (46.7%) below normal in 35, (50.7%) normal in 38, (1.3%) in above normal in a subject and (1.3%) in one obese subject. Conclusion: BIA should be consider when determining body composition in young adults which provides better results than BMI.

Amaç: Sağlıklı genç erişkinlerde, vücut kitle indeksi (VKİ) ve biyoelektrik impedans analiz (BIA) yöntemleri ile vücut yağ durumunun değerlendirilerek iki yöntemin etkinliklerinin ölçülmesidir. Gereç ve Yöntem: Çalışmada yaş ortalaması 20.3±1.2 olan, 246 (171 erkek, 75 kız) öğrencinin vücut kompozisyonları VKİ ve BIA yöntemleri ile ölçülerek değerlendirildi. Bulgular: Cinsiyetlerine göre VKİ'leri erkeklerin 12 tanesinde (%7) 30 kg/m2 idi. Kadınların ise 9 tanesinde (%12) 30 kg/m2 idi. Vücut yağ yüzdeleri ise: erkeklerin 114 tanesi (%66.8) normalin altı, 51 tanesi (%29.9) sağlıklı, 4 tanesi (%2.2) fazla yağlı, 2 tanesi (%1.1) obez grupta idi. Kadınların ise 35 tanesi (%46.7) normal altı, 38 tanesi (%50.7) sağlıklı, 1 tanesi (%1.3) fazla yağlı grupta, 1 tanesi (%1.3) obez grupta yer aldı. Sonuç: Gençlerde VKI kullanılması kişilerin yağ durumunu değerlendirmede yetersiz kalabilmektedir. Bu nedenle vücut kompozisyonunun belirlenmesinde BIA yapılması gereklidir.
GENÇ ERİŞKİNLERDE VÜCUT BİLEŞİMLERİNİN DEĞERLENDİRİLMESİNDE VÜCUT KİTLE İNDEKSİ VE BİYOELEKTRİK İMPEDANS ANALİZİNİN KARŞILAŞTIRILMASI